Faktor yang Berhubungan dengan Kejadian Stunting pada Bayi Usia 6-24 Bulan - Halida Thamrin; Azrida M (FORIKES, 2022)
A developed nation can be realized with the fulfillment of quality human resources. The realization of a quality generation of the nation cannot be separated from health efforts, especially maternal and child health. Stunting are children who experience growth retardation due to poor diet or repeated infections, who tend to have a greater risk of morbidity and mortality. Stunting is a long-term impact of malnutrition, and often results in delayed mental development, poor school performance and decreased intellectual capacity. The purpose of this study was to analyze the factors associated with the incidence of stunting in children aged 6-24 months in the working area of the Bara-Baraya Health Center. The design of this study was cross-sectional. The research subjects were 37 children aged 6-24 months in the working area of the Bara-Baraya Health Center, Makassar City, which were selected by accidental sampling technique. Data was collected by measuring height using a microtoise, interviews and filling out questionnaires by mothers. The data that has been collected was analyzed using the Chi square test. The results showed that there was no relationship between birth weight and the incidence of stunting, there was a relationship between birth length and the incidence of stunting, there was no relationship between a history of exclusive breastfeeding and the incidence of stunting, there was a relationship between a history of infectious diseases and the incidence of stunting, there was a relationship between income families with stunting and there is a relationship between the mother's level of knowledge about nutrition and the incidence of stunting. Thus, the factors of stunting in the working area of the Bara-Baraya Health Center, Makassar City are birth length, history of infectious diseases, family income, and level of knowledge.Keywords: stunting; child; risk factors; birth length; history of infection; income; knowledge ABSTRAK Bangsa yang maju dapat diwujudkan dengan terpenuhinya sumberdaya manusia yang berkualitas. Perwujudan generasi bangsa yang berkualitas tidak dapat terlepas dari upaya kesehatan, khususnya kesehatan ibu dan anak. Stunting merupakan anak-anak yang mengalami retardasi pertumbuhan akibat pola makan yang buruk atau infeksi berulang, yang cenderung memiliki risiko lebih besar untuk morbiditas dan mortaliotas. Stunting adalah dampak kekurangan gizi dalam jangka panjang, dan sering mengakibatkan keterlambatan perkembangan mental, prestasi sekolah yang buruk dan penurunan kapasitas intelektual. Tujuan penelitian ini adalah menganalisis faktor-faktor yang berhubungan dengan kejadian stunting pada anak usia 6-24 bulan di wilayah kerja Puskesmas Bara-Baraya. Desain penelitian ini adalah cross-sectional. Subyek penelitian adalah 37 anak usia 6-24 bulan di wilayah kerja Puskesmas Bara-Baraya, Kota Makassar yang dipilih dengan teknik accidental sampling. Pengumpulan data dilakukan dengan pengukuran tinggi badan menggunakan microtoise, wawancara dan pengisian kuesioner oleh para ibu. Data yang telah terkumpul dianalisis menggunakan uji Chi square. Hasil penelitian menunjukkan bahwa tidak ada hubungan antara berat badan lahir dengan kejadian stunting, ada hubungan antara panjang badan lahir dengan kejadian stunting, tidak ada hubungan antara riwayat ASI eksklusif dengan kejadian stunting, ada hubungan antara riwayat penyakit infeksi dengan kejadian stunting, ada hubungan antara pendapatan keluarga dengan kejadian stunting dan ada hubungan antara tingkat pengetahuan ibu tentang gizi dengan kejadian stunting. Dengan demikian faktor dari stunting di wilayah kerja Puskesmas Bara-Baraya, Kota Makassar adalah panjang badan lahir, riwayat penyakit infeksi, pendapatan keluarga, dan tingkat pengetahuan.Kata kunci: stunting; anak; faktor risiko; panjang badan lahir; riwayat infeksi; pendapatan; pengetahuan